The efficacy of conventional and technology assisted cue exposure therapy for treating substance use disorders: a qualitative systematic review - Thaysen-Petersen, Daniel; Hammerum, Sigurd Krogh; Düring, Signe Wegmann; Larsen, Pia Veldt; Fink-Jensen, Anders; Mellentin, Angelina I. (Frontiers in Psychiatry, 2025)
BackgroundCue Exposure Therapy (CET) is a behavioristic psychological intervention for treating substance use disorders (SUDs). Recently, CET has been examined in technology-assisted formats to increase intervention efficacy. No systematic review has examined the efficacy of different CET formats across types of SUDs.ObjectivesWe aimed to examine the efficacy of CET across SUDs and examine the efficacy of non-technology-assisted (NT-CET) and technology-assisted CET (T-CET).MethodsWe conducted a systematic literature search in MEDLINE, PsycINFO, EMBASE, and the Cochrane Central Register of Controlled Trials up to June 2024. The efficacy of CET was inspected trough a qualitative synthesis and the quality assessment of all the included studies was performed using the Cochrane risk-of-bias tool for randomized trials, version 2.ResultsForty-four controlled trials were identified (NT-CET; n=21; T-CET: n=23). Most studies were conducted on alcohol- and nicotine use disorders. No study reported effect sizes on craving, while one study reported a small effect of NT-CET on alcohol consumption at 6- and 12-months follow-up. Compared to control interventions, CET was found more effective in 41% of the studies that examined cravings, and in 57% of the studies that examined consumption. In these studies, there was on overrepresentation of studies that combined CET with cognitive behavioral therapy (CBT) or CBT-related approaches. Only one study directly compared the effect of NT- and T-CET alcohol craving or consumption and found no difference up to 6 months follow-up. Among NT-CET and T-CET studies, the proportion of studies reporting significantly better outcomes than control interventions were 17% and 60% for craving, respectively, and 38% and 80% for consumption, respectively. High heterogeneity and risk of bias were found among the included studies.ConclusionsAcross the different substance use disorders, most studies found significant reduction in craving and consumption after CET. No conclusions can be made on the efficacy of CET compared to active control interventions, due to limiting reporting of effect sizes. Technology-assisted CET reported significant reduction in craving and consumption relatively more often than conventional CET studies, particularly when delivered in virtual reality. Future high-quality studies are warranted to enable more firm conclusions and quantitative synthesis.Systematic review registrationhttps://www.crd.york.ac.uk, identifier CRD42022308806.